Studi Komparasi Dukungan Sosial Teman Sebaya yang Dirasakan (Perceived Social Support) pada Mahasiswa Perantau & Lokal - Putri, Freliska Adinda; Widodo, Yohannes Heri (Fakultas Psikologi Universitas YARSI, 2024)
Students who migrate and do not migrate have significant differences in characteristics in the fulfillment of early adult tasks. In this case, Perceived Social Support (PSS) plays an important role in helping students overcome stress, strengthen independence, and improve psychological well-being. The researcher then felt compelled to conduct research on this phenomenon in active students in the Yogyakarta area, where the city is a center for students with varied backgrounds. The purpose of this study is to find differences in perceived social support in overseas & local students, measure the level of PSS of overseas students, measure the level of PSS in local students, and identify low scores on PSS scale items as material for self-development training. The type and design of the research used is a quantitative approach using a comparational method. There were 105 respondents involved, all of whom were active students in Yogyakarta. Data collection contained 2 types of questionnaires, namely: 1) Open questionnaire to determine the regional origin of the respondents, and 2) A closed questionnaire in the form of a Likert Scale that serves to measure PSS items. Because the assumption results were not met, the researcher used the Mann Whitney non-parametric t-test. The results of this study are: 1) There is no significant difference in PSS between groups of overseas and local students; 2) The average PSS level of overseas students tends to be in the high category; 3) The PSS level of local students tends to be in the high category; 4) There are 4 questionnaire items with low scores identified, so the guidance topic that can be proposed is themed “Me & Them: Social & Personal Boundaries